Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fpsyg.2020.615010
|View full text |Cite
|
Sign up to set email alerts
|

Lights and Shadows of Trait Emotional Intelligence: Its Mediating Role in the Relationship Between Negative Affect and State Anxiety in University Students

Abstract: Nowadays, students are experiencing difficult and stressful situations due to the Global Pandemic Alert. This changing world can evoke negative emotions that have been traditionally linked to higher anxiety. Researches have been focused on the positive outcomes of trait emotional intelligence (TEI) preventing psychological disorders. However, the possibility that TEI might have a dark side has been neglected. Hence, this study aimed to explore the mediating effect of the three dimensions of TEI in the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 41 publications
4
14
0
8
Order By: Relevance
“…Likewise, regarding the association between PEI and anxiety in the total sample, EA is not always adaptive and at high levels is linked to increased anxiety. These findings are consistent with those found by Guil et al., 31 in undergraduate students. Likewise, this emotional distress could also be accentuated by low EC and ER 31,32 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Likewise, regarding the association between PEI and anxiety in the total sample, EA is not always adaptive and at high levels is linked to increased anxiety. These findings are consistent with those found by Guil et al., 31 in undergraduate students. Likewise, this emotional distress could also be accentuated by low EC and ER 31,32 …”
Section: Discussionsupporting
confidence: 94%
“…Likewise, this emotional distress could also be accentuated by low EC and ER. 31,32 Finally, it was found that a differentiated profile in terms of PEI dimensions in BC survivors may have different results in experienced Moreover, anxiety would be accentuated if, in addition to affecting EC, it also interfered with ER. Thus, taking into account the serial influence of the dimensions of PEI, 30 not discriminating emotions correctly prevents the implementation of strategies aimed at modifying them.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the relationships between variables, our findings suggest the importance of anxiety and stress in the undergraduates, in line with other studies from different parts of the world and for students enrolled on different types of degree courses (Balaji et al, 2019;Belaunzaran, 2019;Cañero et al, 2019;Castañeda 2016;Mohamad et al, 2021;Morales-Rodríguez & Pérez-Mármol, 2019;Musumari et al, 2018;Morales-Rodríguez et al, 2020). Our data confirm that students reporting episodes of anxiety or stress exhibit greater attention to emotions and inability to repair such emotions (Guil et al, 2021), have difficulties in overall emotion regulation and on most of the subscales (Hallion et al, 2018), and present less effective coping strategies, as shown by their scores on some of the COPE subscales, such as: venting, self-blame and lower positive reframing (Masha'al et al, 2022). Empathy, however, was higher among students with anxiety or stress, such that, as suggested (Pittelkow et al, 2021), there exists hypersensitivity to the emotional signals of others, excessive empathic functioning, with over-attribution of others' mental states and a greater sense of alertness among students with anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…Emotional intelligence has been found to be associated with mental and physical health 14 , subjective wellbeing, optimism, and happiness [15][16][17] . Emotional intelligence seems to operate as a protective factor against depressed mood 18,19 and the development of anxiety symptoms 20,21 . Individuals with high emotional intelligence could be better able to buffer the effects of stress to maintain and protect mental health 22 .…”
Section: Openmentioning
confidence: 99%